2012
DOI: 10.1016/j.immuni.2012.05.030
|View full text |Cite
|
Sign up to set email alerts
|

The BH3-Only Proteins Bim and Puma Cooperate to Impose Deletional Tolerance of Organ-Specific Antigens

Abstract: Summary Although the pro-apoptotic BH3-only protein, Bim, is required for deletion of autoreactive thymocytes, Bim-deficient mice do not succumb to extensive organ-specific autoimmune disease. To determine whether other BH3-only proteins safeguard tolerance in the absence of Bim, we screened mice lacking Bim alongside other BH3-only proteins. Most strains showed no additional defects, however, mice deficient for both Puma and Bim spontaneously developed autoimmunity in multiple organs and their T-cells could t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
82
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(86 citation statements)
references
References 48 publications
(79 reference statements)
2
82
2
Order By: Relevance
“…Through interactions with pro-and antiapoptotic Bcl-2 family members at mitochondria, Bim promotes release of cytochrome c and subsequent caspase activation. Unlike the critical role of Bim in TRA-mediated clonal deletion (15,16), Bim is not required for deletion in the HY cd4 model or other UbA-driven models (12,15,17). However, we found that Bim was essential for caspase-3 activation in thymocytes, suggesting that clonal deletion in HY cd4 Bim 2/2 mice was mediated by a caspase-independent cell death mechanism.…”
contrasting
confidence: 64%
See 1 more Smart Citation
“…Through interactions with pro-and antiapoptotic Bcl-2 family members at mitochondria, Bim promotes release of cytochrome c and subsequent caspase activation. Unlike the critical role of Bim in TRA-mediated clonal deletion (15,16), Bim is not required for deletion in the HY cd4 model or other UbA-driven models (12,15,17). However, we found that Bim was essential for caspase-3 activation in thymocytes, suggesting that clonal deletion in HY cd4 Bim 2/2 mice was mediated by a caspase-independent cell death mechanism.…”
contrasting
confidence: 64%
“…In support of this, phosphorylation and subcellular localization of Nur77 have been shown to be different between stimulated DP thymocytes and mature CD8 + T cells (48). Likewise, in contrast to its lesser impact on UbA-mediated clonal deletion, Bim deficiency is known to block TRA-mediated deletion of CD8SP thymocytes (15,16). Given these context-dependent differences in the mechanism of clonal deletion, it would be of interest to assess the role of Nur77 in TRA-mediated deletion of CD8SP thymocytes as well.…”
Section: Discussionmentioning
confidence: 92%
“…However, it is interesting to note that absence of Bim or overexpression of Bcl2/Bcl-Xl does not phenocopy the severe autoimmune pathology that occurs when negative selection is abrogated from loss of Aire expression (20). In fact, recent evidence suggests that additional loss of NOXA and PUMA is a requirement for autoimmune manifestation in Bimdeficient thymocytes (21), implying redundancy between BH3-only proteins during negative selection. We see little detectable expression of NOXA and PUMA in DP2 thymocytes in our system.…”
Section: Applying Apoptotic Stress To Thymocytes Preferentially Perturbsmentioning
confidence: 99%
“…Indeed, transcriptional upregulation of Noxa has been observed following the activation of both B-and T-cell antigen receptors and a co-operative role in T-cell receptor (TCR) stimulationinduced apoptosis has been demonstrated alongside Bim and Puma. 26,27,30,56 Furthermore, Noxa appears to sensitize lymphocytes with low-affinity antigen receptors toward cell death during the germinal center reaction. 26 Such observations, along with our own, imply the existence of a conserved pathway linking antigen receptor activation to transcriptional regulation of Bim and Noxa.…”
Section: Discussionmentioning
confidence: 99%
“…Bim and Puma) causes more severe defects than loss of Bim alone. 24,30 Such observations indicate that Bim represents the major, but not the sole, apoptotic regulator of B-cell homeostasis.…”
mentioning
confidence: 99%